Seismic wave propagation in anisotropic ice - part 2: effects of crystal anisotropy in geophysical data - Diez, Anja; Binder, Tobias (The Cryosphere, 2015)
We investigate the propagation of seismic waves in anisotropic ice. Two effects are important: (i) sudden changes in crystal orientation fabric (COF) lead to englacial reflections; (ii) the anisotropic fabric induces an angle dependency on the seismic velocities and, thus, recorded travel times. Velocities calculated from the polycrystal elasticity tensor derived for the anisotropic fabric from measured COF eigenvalues of the EDML ice core, Antarctica, show good agreement with the velocity trend determined from vertical seismic profiling. The agreement of the absolute velocity values, however, depends on the choice of the monocrystal elasticity tensor used for the calculation of the polycrystal properties. We make use of abrupt changes in COF as a common reflection mechanism for seismic and radar data below the firn-ice transition to determine COF-induced reflections in either data set by joint comparison with ice-core data. Our results highlight the possibility to complement regional radar surveys with local, surface-based seismic experiments to separate isochrones in radar data from other mechanisms. This is important for the reconnaissance of future ice-core drill sites, where accurate isochrone (i.e. non-COF) layer integrity allows for synchronization with other cores, as well as studies of ice dynamics considering non-homogeneous ice viscosity from preferred crystal orientations.
Gesehen am 28.05.2020